Pengaruh Kemudahan dan Kualitas terhadap Penggunaan Sistem Informasi Akuntansi pada Usaha Kecil dan Menengah di Kabupaten Banyumas - Bambang Setyobudi Irianto (Jurnal Riset Akuntansi Soedirman, 2026)
The development of information technology requires MSMEs to digitalize financial records through Accounting Information Systems. However, the level of AIS usage among MSMEs in Banyumas Regency is still low. This study aims to examine the effect of Ease of Use and AIS Quality on the Use of AIS in MSMEs in Banyumas Regency. This study uses a quantitative approach with a survey method. The population in this study is all MSMEs in Banyumas Regency that use Accounting Software. The research sample consisted of 62 respondents selected using purposive sampling technique. Data analysis techniques used multiple linear regression analysis with the help of SPSS. The results of the study show that Ease of Use has a positive and significant effect on AIS Usage. AIS Quality has a positive and significant effect on AIS Usage. The implication of this study is that software developers need to improve ease of use and ensure information quality so that AIS can be widely adopted by MSMEs.